Vitamin D and pulmonary function in obese asthmatic children. Issue 12 (6th June 2016) - Lautenbacher, Laura A.; Jariwala, Sunit P.; Markowitz, Morri E.; Rastogi, Deepa
Summary: Objective: Asthma‐related morbidity is higher among children with vitamin D deficiency and obesity, morbidities that frequently co‐exist among minority children. However, the effect of co‐existent obesity and vitamin D deficiency on pulmonary function is poorly understood. Methods: We compared percent‐predicted values of pulmonary function across vitamin D categories among 72 obese and 71 normal‐weight Hispanic and African‐American children with asthma recruited at an urban children's hospital. Serum cytokines associated with Th1 and Th2 inflammation and 25‐hydroxyvitamin D (25‐OHD) were quantified in fasting serum. 25‐OHD levels ≥30 ng/ml were categorized as sufficient, <30 and ≥20 ng/ml as insufficient, and <20 ng/ml as deficient. The role of inflammation was investigated by regression analysis. Results: Vitamin D deficiency was present in 50% of children and did not differ by obese status. Forced Expiratory Volume in the first second (84.5 ± 9.4 vs. 94.8 ± 8.4, P  < 0.001), and Functional Residual Capacity (67.5 ± 20.1 vs. 79.3 ± 19, P  = 0.01) were lower among vitamin D deficient obese asthmatics than their sufficient counterparts, and Total Lung Capacity was lower than their insufficient counterparts (86.9 ± 14.3 vs. 96.6 ± 10, P  = 0.01); similar associations were not observed in normal‐weight asthmatics and were not influenced by systemic inflammation. No association between Th1 and Th2 inflammatory measures, vitamin D deficiency, and pulmonary function tests was found. Conclusions: Vitamin D deficiency was associated with pulmonary function deficits among obese children, but not among normal‐weight children with asthma, an association that was independent of Th1 and Th2 serum inflammatory measures. Vitamin D deficiency may be one potential mechanism underlying the obese‐asthma phenotype.Pediatr Pulmonol. 2016;51:1276–1283. © 2016 Wiley Periodicals, Inc.